Godkiller - Kaner, Hannah (Harper Voyager, 2023)
Gods are forbidden in the kingdom of Middren. Formed by human desires and fed by their worship, there are countless gods in the world--but after a great war, the new king outlawed them and now pays "godkillers" to destroy any who try to rise from the shadows. As a child, Kissen saw her family murdered by a fire god. Now, she makes a living killing them and enjoys it. But all this changes when Kissen is tasked with helping a young noble girl with a god problem. The child's soul is bonded to a tiny god of white lies, and Kissen can't kill it without ending the girl's life too. Joined by a disillusioned knight on a secret quest, the unlikely group must travel to the ruined city of Blenraden, where the last of the wild gods reside, to each beg a favor. Pursued by assassins and demons, and in the midst of burgeoning civil war, they will all face a reckoning. Something is rotting at the heart of their world, and they are the only ones who can stop it.